Differences and similarities in adolescents' academic motivation across socioeconomic and immigrant backgrounds. (November 2021) - Manganelli, Sara; Cavicchiolo, Elisa; Lucidi, Fabio; Galli, Federica; Cozzolino, Mauro; Chirico, Andrea; Alivernini, Fabio
Abstract: The study, based on Self-Determination Theory (SDT), investigated the similarities and differences in the academic motivation of adolescents with different socioeconomic status (SES) and immigrant backgrounds. Exploratory Structural Equation Modelling (ESEM) analyses were conducted on data from a representative sample of 26, 598 Italian adolescents. While the structure of academic motivation proposed by SDT (i.e. the self-determination continuum) proved to be invariant across different SES and immigrant backgrounds, different groups were characterised by specific types of motivation. Adolescents with a low SES had lower levels of intrinsic motivation and identified regulation, together with higher levels of amotivation and external regulation than their peers with high SES. Immigrant adolescents had lower levels of identified regulation and higher levels of amotivation, external and introjected regulation than natives. While confirming the universality of the structure of motivation postulated by SDT, our findings show that in disadvantageous social and economic conditions the more self-determined forms of motivation can be weakened, thereby exacerbating the difficult conditions of disadvantaged adolescents.